2016
DOI: 10.4047/jap.2016.8.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Power spectrum density analysis for the influence of complete denture on the brain function of edentulous patients - pilot study

Abstract: PURPOSEThis pilot study was to find the influence of complete denture on the brain activity and cognitive function of edentulous patients measured through Electroencephalogram (EEG) signals.MATERIALS AND METHODSThe study recruited 20 patients aged from 50 to 60 years requiring complete dentures with inclusion and exclusion criteria. The brain function and cognitive function were analyzed with a mental state questionnaire and a 15-minute analysis of power spectral density of EEG alpha waves. The analysis includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…They reported that chewing was an effective method to stimulate the brain. Perumal et al, 2016 [27] added that restoration of occlusion and masticatory function with satisfactory dentures stimulates the brain activity via trigeminal nerve [27], [15]. Furthermore, the comparative results revealed that the effect of either increasing or decreasing VDO on alpha waves was insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that chewing was an effective method to stimulate the brain. Perumal et al, 2016 [27] added that restoration of occlusion and masticatory function with satisfactory dentures stimulates the brain activity via trigeminal nerve [27], [15]. Furthermore, the comparative results revealed that the effect of either increasing or decreasing VDO on alpha waves was insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…Valipour et al ( 18 ), Vialatte et al ( 19 ) displayed the use of EEG and PSD in obtaining improved data when compared to other methods . PSD is an established method of evaluating EEG ( 9 , 19 , 20 ) and spectral parameters can be achieved from all available EEG machines. The use of spatial filters, canonical correlation analysis (CCA) and blind source separation technique (BSS) can effectively reduce the artefacts that might arise with this technique ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…“10-20 electrode placement system” was employed for the procedure which is a standardisation for electrode placement. This standardisation was provided by the international federation in electroencephalography (IFCN) and clinical neurophysiology ( 9 ). EEG recordings were made in three stages.…”
Section: Methodsmentioning
confidence: 99%